Factors influencing social media usage among Farm youth in rural communities of Federal Capital Territory (FCT), Nigeria - Oluyaire, Bankole; A. A. , Adetunji; L. G. , Lapkat; A. F. , Aderounmu; C. O. , Akure; O. O. , Samson; Danbaki, C. A.; G. , Lukman; S. B. , Abdulkarim; Bako , Amos (Advances in Social Sciences Research Journal, 2020)
The study assessed factors influencing social media usage for agricultural information dissemination among farm youth in rural communities of the Federal Capital Territory (FCT), Nigeria. Multi-stage sampling was used to select 212 respondents. Structured interview schedule was used to collect data, and analysed with descriptive statistics and factor analysis. The result from the study showed that majority (59.9%) of the farm youth were between the ages of 15 and 24 years with mean age range of 23.82.76, 68% had completed secondary school while 68% practiced Christianity. The study further identified socioeconomic and social media related as two factors that emerged from factor analysis of ten variables. The study recommended that the use of social media for agricultural information dissemination should consider users’ education, values and culture as well as the availability and accessibility of the media and, the level of knowledge of social media the beneficiaries have for maximum benefit.